IPSec: The New Security Standard for the Internet, Intranets, and Virtual Private Networks, Second Edition - Doraswamy, Naganand (Prentice Hall PTR, 2011)
IPsec offers the strongest security available to companies seeking to build VPNs and other applications that deliver confidential information across the Internet. This is the most authoritative, comprehensive guide to IPsec available -- authored by its first implementers, and active participants in the IPsec standards process. First, review the fundamentals of computer and network security, and the tradeoffs associated with implementing security at each layer of the IP stack. Next, walk through IPsec's architecture and components; the role of authentication, encryption, encapsulating security payloads (ESPs), and key management protocols. Learn how IPsec addresses security in host-to-host, host-to-gateway, and gateway-to-gateway configurations; and in VPN tunneling. Review detailed scenarios, discovering how to implement IPsec in VPNs, nested tunnels, chained tunnels, and overlapping security associations. Finally, preview the future of IPsec, with timely coverage of compression, multicast, mobility, and more.